Continuum of care of mothers and immunization status of their children: A secondary analysis of 2015-2016 Myanmar Demographic and Health Survey - Phway Phway; Aung Tin Kyaw; Aye Sandar Mon; Kyaw Swa Mya (Elsevier, 2022)
Objective: To assess the association between the continuum of care of mothers and the immunization status of their 12-23 months old children. Study design: A secondary data analysis using the Myanmar Demographic and Health Survey (2015-16) data, a cross-sectional, household-based, nationally representative survey conducted during 2015-2016. Methods: We included 1669 pairs of mothers and their children in this analysis. We categorized the children into fully immunized and no/not fully immunized children and define a continuum of care (CoC) of the mother if women received antenatal care ≥ four times, delivered with skilled birth attendances, and received postnatal care within 48 h after delivery. We used the multivariable binary logistics regression using STATA version 15.1 with the survey command (svy) and reported the results by adjusted odds ratios (aORs) with 95% confidence intervals (CIs). Results: The mother's CoC prevalence was 42.5%, and that of fully immunized children was 33.5%. However, only one-fifth of mothers and their children received the continuum of care services altogether. The children of mothers who received CoC were more likely to be fully vaccinated than those who did not (aOR = 1.60, 95%CI: 1.21, 2.13, P < 0.001). The child's birth order, employment status, and wealth status of the households are independent predictors of the full immunization of children. Conclusions: We concluded that receiving the CoC in mothers influenced their children's vaccination status. Hence, integrating maternal health programs and immunization programs is essential to achieving sustainable development goals in Myanmar.